Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de Medicina Veterinaria de la facultad agropecuaria y de los recursos naturales renovables de la Universidad Nacional de Loja, 2023-2024 - Campoverde Córdova, Nixon Adrián (2024)
The issue of low levels of attention and memory, and the level of reading comprehension among university students is a problem that educators should pay attention to. Therefore, the objective of this curriculum integration work focused on analyzing the relationship between the level of basic cognitive processes of attention and memory, and reading comprehension in first-year students of the Veterinary Medicine program. The study conducted was a quantitative, descriptive, non-experimental, cross-sectional design. The d2 Test, the RIAS test subscale, and the ICLAU instrument were applied to evaluate attention, memory, and reading comprehension in the selected sample of 39 students. Statistical analysis was performed using SPSS version 25, considering the Tau-b Kendall rank correlation coefficient, and the p-value was interpreted on the Pearson correlation coefficient scale. The study found that 92.31% of students exhibit low levels of attention; however, 51.28% of the sample reached a medium level in memory, and 43.59% reached a high level. Meanwhile, 74.36% achieved a low level in reading comprehension, and 17.95% achieved a high level, with these results being significant. Finally, the correlation between attention and reading comprehension reached a Kendall's Tau-b value of 0.46, and memory with reading comprehension had a Kendall's Tau- b value of 0.39. It is concluded that there is a medium-sized positive correlation between basic cognitive processes and reading comprehension. Thus, the alternative hypothesis is accepted, and the null hypothesis is rejected.